Zakat as a Tax Reduction in the Framework of Realizing Indonesia as a Welfare State: Zakat sebagai Pengurangan Pajak dalam Kerangka Mewujudkan Indonesia sebagai Negara yang Sejahtera - Zuhdi, Syaifuddin; Rauf, Aulia Lestari; Astuti, Widi (QISTHOSIA : Jurnal Syariah dan Hukum, 2024)
Indonesia, as a country with the largest Muslim population, has significant potential in integrating zakat as a complementary social welfare instrument to national tax policy. This article aims to disclose the implementation of zakat as a tax deduction in leading Indonesia to be a welfare state. This study uses a normative legal approach with a conceptual method to explore the potential for integrating zakat as an income tax deduction, in order to achieving a more equitable and inclusive distribution of welfare. The data used is secondary data in the form of documents, both those included in the category of primary legal materials such as regulations or secondary legal materials such as books and journals. The main findings of the study indicate that the concept of a welfare state in general seeks to realize public welfare through equitable distribution and public policies based on the principle of benefit for all citizens. and recognizing zakat as an income tax deduction can improve social justice for Muslims and strengthen national fiscal independence through direct optimization of welfare distribution. This approach is expected to not only increase active community participation in state policies, but also accelerate poverty alleviation and reduce the country's dependence on external financing. Thus, this study offers a synergistic model between zakat and taxes that has the potential to create a sustainable and inclusive welfare system for all levels of society.